2020
DOI: 10.1186/s13017-020-00341-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SARS-CoV-2 pandemic on emergency surgery services—a multi-national survey among WSES members

Abstract: Background The SARS-CoV-2 pandemic is a major challenge for health care services worldwide. It’s impact on oncologic therapies and elective surgery has been described recently, and the literature provides guidelines regarding appropriate elective patient treatment during the pandemic. However, the impact of SARS-CoV-2 pandemic on emergency surgery services has been poorly investigated up to now. Methods A 17-item web survey had been distributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 27 publications
10
74
2
3
Order By: Relevance
“…The electronic questionnaire was created starting from a research protocol shared within the steering committee. Most questions were linked to previous studies in the fields of trauma and emergency surgery [ 10 , 16 , 17 ], knowledge management and organization science [ 3 , 18 , 19 ], and clinical ethics [ 4 , 17 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The electronic questionnaire was created starting from a research protocol shared within the steering committee. Most questions were linked to previous studies in the fields of trauma and emergency surgery [ 10 , 16 , 17 ], knowledge management and organization science [ 3 , 18 , 19 ], and clinical ethics [ 4 , 17 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Baseline demographics of trial groups are shown in table (1).Groups included 419 patients, 212 (50.6%) of them were males and 207 (49.4%) females.The age groups ranged from (13)(14)(15)(16)(17)(18) to (> 65) years.Table (2) showed the effectiveness of black seeds on covid-19 among the participants. Cross tabulation was performed to describe the association between black seeds group and severity as well as the final outcome of infection with covid19.…”
Section: Resultsmentioning
confidence: 99%
“…COVID19 storm shows its lethal face worldwide and it is still difficult to predict how long it will last, and how deadly it could be (1) . This disease mainly affected social life, particularly health care services in addition to daily treatment practices since the world health organization (WHO) declared SARS CoV-2 as a global pandemic in early 2020 (2)(3)(4)(5) . The COVID-19 infection primarily affects the respiratory system and is presented with cough, fever and sometimes pneumonia and shortness of breath and patients may deteriorate due to acute respiratory distress syndrome, as well as other clinical manifestations such as cardiac, gastrointestinal and central nervous system (6)(7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus pandemic has a huge impact on the health care system, including access, delivery and utilisation of health care [ 29 31 ]. For example, patients with chronic diseases, acute health events or emergencies may not seek health care during the pandemic with a potential negative impact on longterm health outcomes [ 32 36 ]. In general, patients are more likely to be fearful of seeking health care professional advice, non-elective treatments are postponed, and intensive care units in hospitals face an alarming situation with COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%